Impact of Enriched Environment on Murine T Cell Differentiation and Gene Expression Profile - Rattazzi, Lorenza; Piras, Giuseppa; Brod, Samuel; Smith, Koval; Ono, Masahiro; D’Acquisto, Fulvio (Frontiers in Immunology, 2016)
T cells are known to be plastic and to change their phenotype according to the cellular and biochemical milieu they are embedded in. In this study we transposed this concept at a macroscopic level assessing whether changes in the environmental housing conditions of C57/BL6 mice would influence the phenotype and function of T cells. Our study shows that exposure to two weeks in an enriched environment does not impact the T cell repertoire in vivo and causes no changes in the early TCR-driven activation events of these cells. Surprisingly, however, T cells from enriched mice showed a unique T helper effector-cell phenotype upon differentiation in vitro. This was featured by a significant reduction in their ability to produce IFN-γ and by an increased release of IL-10 and IL-17. Microarray analysis of these cells also revealed a unique gene fingerprint with key signaling pathways involved in autoimmunity being modulated. Together our results provide first evidence for a specific effect of enriched environment on T cell differentiation and its associated changes in gene expression profile. In addition, our study sheds new light on the possible mechanisms by which changes in environmental factors can significantly influence the immune response of the host and favor the resolution of the inflammatory response.